2021
DOI: 10.1038/s41598-021-97925-w
|View full text |Cite
|
Sign up to set email alerts
|

A novel antioxidant ergothioneine PET radioligand for in vivo imaging applications

Abstract: Ergothioneine (ERGO) is a rare amino acid mostly found in fungi, including mushrooms, with recognized antioxidant activity to protect tissues from damage by reactive oxygen species (ROS) components. Prior to this publication, the biodistribution of ERGO has been performed solely in vitro using extracted tissues. The aim of this study was to develop a feasible chemistry for the synthesis of an ERGO PET radioligand, [11C]ERGO, to facilitate in vivo study. The radioligand probe was synthesized with identical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Next, reductive methylation of a primary amine with aldehyde and sodium cyanoborohydride produced intermediate 4 with good yield. The incorporation of the thioketone into the imidazole ring and protection of the active functional groups in imidazole ring with Boc groups were performed as described in the past to provide precursor 6 [6].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, reductive methylation of a primary amine with aldehyde and sodium cyanoborohydride produced intermediate 4 with good yield. The incorporation of the thioketone into the imidazole ring and protection of the active functional groups in imidazole ring with Boc groups were performed as described in the past to provide precursor 6 [6].…”
Section: Resultsmentioning
confidence: 99%
“…Basically, to set the stage for the crucial incorporation of the thiol group onto imidazole, the amino and carboxyl groups of histidine were blocked with acidic labile moieties, while the imidazole amine was protected with an Fmoc group. We previously reported that the amine‐protecting Boc groups could be removed using TFA in the presence the t ‐butyl ester at −78 °C [6]. This reaction confers good yield, albeit only with stringent operations and attention to detail.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even 30 min after injection of 11 C‐labeled ET (PET radioligand) into the tail of Alzheimer's model mice, relatively little was found in the brain (external fig. 6) [99]. Uptake in the kidney was 12‐fold higher and in the liver 8‐fold higher.…”
Section: Important Ett Expression Sitesmentioning
confidence: 99%